Genre, environnement et conflit à Plogoff (1980) - Vincent Porhel (Genre & Histoire)
The links between conflict, environment and gender issues are still little discussed in France. This article, by considering an environmental struggle in Brittany in and around 1968, shows the complex relationship between male representations based on the mastery of science and technology and a female will to oppose the implementation of projects perceived as a risk to the immediate environment. As such, the article challenges ecofeminism by highlighting the diversity of actions led by the women of Plogoff, which are not reducible to a feminist positioning. These actions, which resulted in a victory for the opponents of the project of nuclear power station in 1980, lead to an arrangement of memories which confuses the commitment of women, the environment and the defence of a regional identity.